The Business Intelligence impact on the financial performance of start-ups - Huang, Z.-X. (Elsevier Ltd, 2022)
Business Intelligence goal is to investigate, integrate and logically collect and multidimensional analysis of data from varied customer information sources, environment, competitors, markets, and etc. to enhance the performance of businesses, particularly startups. This research aims to study the impact of Business Intelligence on the financial performance of start-ups. The method is descriptive-survey, aside practical purpose. The study statistical population covered CEOs and experts of startup companies who were investigated in a 250-sample people. Also, 43-item questionnaire aside set up validity with confirmatory factor analysis, and validity analysis was employed for data collection. The results indicated that Business Intelligence did not impact Network Learning in startups, however, Business Intelligence enhanced Innovativeness in startups by 0.99, also, Innovativeness enhanced the financial performance of startups by 0.311, startups intelligence on Network Learning by 0.537, Network Learning on enhancing Innovativeness in startups by 0.632, and Network Learning on financial performance enhancement in startups by 0.397. The impact of Business Intelligence on Innovativeness as well as Network Learning confirmed, also, the impact of Innovativeness and Network Learning on financial performance confirmed. Thus, it can be concluded that the impact of Business Intelligence on financial performance has been studied indirectly through the mediating role of Innovativeness and Network Learning in startups. Surprisingly, these two factors are necessary to enhance financial performance. Â© 2021 Elsevier Ltd